IMPLEMENTASI NILAI-NILAI PANCASILA PADA MINAT WIRAUSAHA (STUDI KASUS KNPI KOTA SEMARANG) - ahmad zaenal arifin (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2020)
ABSTRACTPancasila is the basis for the nation of Indonesia. The application of Pancasila values in entrepreneurship will encourage new entrepreneurs who grow in accordance with the culture that develops in Indonesia as a populist economy characterized by Indonesia. The existence of Pancasila entrepreneurship in the form of a populist economy can encourage the creation of new jobs so that it can be a solution in reducing unemployment. Entrepreneurs can be formed and trained, so the most important one is the existence of entrepreneurial intention. Therefore, it is important to know the determinants of entrepreneurial intention. One approach to look at the factors that influence interest in entrepreneurship is through Theory of Planned Behavior (TPB). There are three main components in TPB, which are attitude, social norm and perceived behavioral control. This study aims to: analyze the effect of the perceived implementation of Pancasila to attitude; analyze the effect of perceived implementation of Pancasila to perceived behavioral control; analyze the effect of the perceived implementation of Pancasila to social norms; analyze the effect of attitude to entrepreneurial intention; analyze the effect of perceived behavioral control to entrepreneurial intention; analyze the influence of social norm to entrepreneurial intention; analyze the effect of access to entrepreneurial intention; analyze the effect of access to entrepreneurial action; analyze the effect of entrepreneurial intention on entrepreneurial action.